Post-Truth dan Generasi Digital: Mengurai Tantangan Literasi Informasi di Era Disinformasi - Muhammad Rasyad Ghazali Saraan; OK Dedy Arwansyah; Armansyah Matondang; Agung Suharyanto (Universitas Medan Area, 2025)
The post-truth era is characterized by the erosion of the role of facts in shaping public opinion, which is increasingly replaced by personal emotions and beliefs. The younger generation, as the dominant users of social media, faces serious challenges in sorting out accurate information amid the dominance of emotional content, algorithms that create echo chambers, and digital social pressures. This study employs a descriptive-qualitative approach based on literature studies to identify the main challenges faced by the younger generation and formulate strategies to improve information literacy. The study's results show that low media literacy, digital fatigue, a crisis of trust in institutions, and the weak integration of media literacy in formal education all contribute to increased vulnerability to disinformation. Therefore, a systemic approach is needed through the collaboration of various parties to form a healthy information ecosystem and strengthen the resilience of the digital generation to information manipulation.